Developing and Implementing Instrumentation for Digital High School Curricula: A Regional Study of a Rubric for Instructional Quality - Rachel Vannatta Reinhart; Savilla Banister (Athens Institute for Education and Research, 2018)
As our world has continued to become more dependent on digital communication and collaboration, online learning environments have become more sophisticated. Demand for online and/or hybrid learning materials has increased, not only in higher education arenas, but in elementary and secondary schools, as well. This study describes the development and implementation of an evaluative rubric for high school digital curricula created for a United States regional consortium of school districts, charged with expanding quality digital learning environments for their students. Digital instructional units for ten high school courses were created by collaborative teacher design teams, with each team consisting of 4-7 teachers. With the goal of creating 1/3 of a year's curriculum, teams developed 2-4 units per course in the first year. A total of 30 units were developed and evaluated. In collaboration with project partners, developed the NWOi3 Evaluation Rubric for Digital Curriculum that was used to assess curriculum units and consisted of 36 criteria organized by eight areas: 1) Overview, 2) Learning Targets, 3) Instructor Support, 4) Accessibility, 5) Instructional Materials, 6) Learner Interaction and Engagement, 7) Technology, and 8) Assessment. A variety of sources contributed to rubric development: Quality Matters K-12 Secondary Rubric (Quality Matters, 2017), Blended Course Peer Review Form (Blended Learning Toolkit, 2014), and the National Standards for Quality Online Programs (International Association for K-12 Online Learning [iNACOL], 2011). The evaluation process utilized a team of reviewers: five content experts, and three curriculum/ technology experts. A third evaluator then summarized the two reviews for every unit, providing a score for each criterion along with detailed comments and feedback. The process of how rubric results were analyzed and reported is described along with the challenges encountered.